(3efGQGJ GdSGFQjf hebGeGJ GdWGFQjfs - (3CHh HcQ YHO Gddg Hf eMeO Hf TGgGhQ GdGSOj GdQGRjs
(3ChdgG (B:s
(3GdMeO ddg GdefaQO ai UaGJg GdeHOY ai eHOYGJg GdeHOF ai eNJQYGJg GdPi Ndb HHOjY aWQJg hUfjY MceJg CeG HYO abGd TjNfG CHh HcQ YHO dGdg Hf eMeO Hf TGgGhQ GdCSOi GdQGRi Cf Ufa cJGHkG cGedkG s
(3BNQgG (B:s
(3MJi SGb Edjg GdbOQ GdcGTa Yf YfGOI GdbOje ai Mb GdWGdH GdUGOb ai bUQ GdWQjb Gdbhje hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO NGJe GdCfHjGA hGdeQSdjf hYdi Bdg hUMHg CLeYjf MSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3djOf (B(702) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs